(untitled) (Revista Contexto & Educação, 2025)
The aim of this article is to identify, describe and analyse the sequence of ritualized actions that is part of the management of Unifesp’s Pre-PEC-G program, a preparatory course intended to welcome and teach Portuguese as an additional language to PEC-G students. It is a systematization of experience considering the interconnected actions of teaching, research, extension and management involved in this program at Unifesp and it is based on the writing of memories of the multiple dimensions of the lived experiences during its implementation, document and bibliographic analysis. The discussion develops in order to indicate how it is possible to face challenges and to build a plural and critical democratic management in higher education, characterized by: collectivized and implicated management, articulation of collaborative networks, intercultural and intersectional reflexivity and what we call here as taming of management, based on Célia Xakriabá The results point out to the challenges of management in intercultural contexts and the potential of interdisciplinary actions in the construction of welcoming and language teaching policies in cooperation projects aimed at international students.